The Impact of Transformational Leadership on Organisational Commitment Among Physical Education Teachers (Istanbul Province Example) - Çutuk, Selman; Coban, Eser (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
This study aims to explore the relationship between transformational leadership and organizational commitment and assess its impact on physical education teachers. The research utilized the transformational leadership and organizational commitment scales, which were validated by Bozkurt (2022). Bozkurt (2022) also developed the questionnaire incorporating both scales. Data collection was conducted through online platforms and face-to-face interviews. The sample consisted of 202 physical education teachers working in various schools and institutions affiliated to the Ministry of National Education in the province of Istanbul, determined through convenience sampling.The data were analyzed using SPSS 25.0. An independent t-test was applied to compare continuous data between two groups, while One-Way ANOVA was used for multiple groups. Post-hoc tests were conducted to identify group differences after ANOVA. The relationship between continuous variables was examined using Pearson’s correlation coefficient. The findings indicate a significant, moderate, and positive relationship between .46 transformational leadership and organizational commitment among physical education and sports teachers.